Immediate overdenture for improving aesthetic of anterior teeth with periodontal problem - FX. Ady Soesetijo (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: The construction of overdenture is often applied because endodontic treatment usualy give very promising results and patient has high motivation to maintain their natural teeth. Overdenture is a removable partial or complete denture that covers and rests on one or more remaining natural teeth, roots and/or dental implants. The presence of retained teeth can maximize retention, stabilization and prevent trauma to the oral mucosa. Meanwhile, the presence of root in the bone can delay resorption of the alveolar process. The role of proprioceptor in the periodontal ligament abutment teeth remains effective. Thus, it can be said the overdenture treatment is a preventive prosthodontic treatment. Purpose: The purpose of this case report was to present a case of maxillary and mandibullary anterior teeth with periodontal disease, through endodontic and prosthodontic treatments for recovering its function of phonetic and aesthetic. Case: The 25 years old female with periodontal problems (protrusive, wiggly °1–°2 and along with gingival retraction) on 12, 11, 21, 22 and 32, 31, 41, 42. The patient felt bad about his performance and affect his self confidence. The patient visited tthe dental hospital to restore her teeth and recovering aesthetic and phonetic functions. Case management: The overdenture inserted immediately after one visit endodontic treatment and cutting off the clinical crown of the teeth. The adaptation of the denture is needed by relining using self cured acrylic resin. The patient was quite satisfied with the treatment. Conclusion: In conclusion, the maxillary and mandibullary anterior teeth with periodontal problem could be managed through conservative and prosthotontic approach of treatment to recover of its performance and function.Latar belakang: Konstruksi overdenture sering diaplikasikan pada pasien, karena perawatan endodontik memberikan hasil perawatan yang sangat menjanjikan dan pasien memiliki motivasi tinggi untuk mempertahankan gigi asli mereka. Overdenture adalah gigi tiruan lepasan sebagian atau lengkap yang bertumpu pada satu atau lebih gigi asli yang tersisa, akar dan/atau implan gigi. Gigi asli yang tersisa di dalam mulut dapat memaksimalkan retensi, stabilisasi dan mencegah trauma pada mukosa oral. Selain itu, dipertahankannya sisa akar gigi dapat menghambat resorpsi tulang alveolar serta peran proprioseptor ligamen periodontal tetap efektif. Dengan demikian, dapat dikatakan bahwa perawatan overdenture adalah perawatan prostodontik pencegahan. Tujuan: Tujuan dari laporan kasus ini adalah untuk mempresentasikan kasus gigi-gigi anterior rahang atas dan rahang bawah dengan penyakit periodontal melalui perawatan endodontik dan prostodontik untuk memulihkan fungsi fonetik dan estetik. Kasus: Wanita usia 22 tahun dengan masalah periodontal (protrusi, goyang °1–°2 dan disertai dengan retraksi gingival) pada 12, 11, 21, 22 dan 32, 31, 41, 42. Pasien datang ke rumah sakit gigi dan mulut ingin memperbaiki giginya untuk mengembalikan fungsi estetik dan fonetik. Pasien merasa kurang percaya diri terhadap penampilannya. Tatalaksana kasus: Overdenture dipasang segera setelah perawatan one visit endodontik yang diikuti dengan pemotongan mahkota klinis. Relining dengan resin akrilik diperlukan untuk menyesuaikan gigi tiruan terhadap jaringan pendukungnya. Pasien cukup puas dengan perawatan ini. Kesimpulan: Disimpulkan bahwa, gigi-gigi anterior rahang atas dan rahang bawah dengan masalah periodontal dapat diperbaiki melalui pendekatan perawatan konservasi dan prostodonsi untuk memperbaiki penampilan dan fungsi.